Working during the COVID-19 pandemic: Demands, resources, and mental wellbeing - Scheel, Tabea Eleonore; Bendixen, Lydia; Procházka, Jakub; Acquadro Maran, Daniela (Frontiers in Psychology, 2023)
The aim of this study was to investigate the relationship between working conditions at the start of the COVID-19 pandemic (spring 2020) and employees’ mental wellbeing. According to the Job Demands-Resources (JD-R) model, work intensification, increased difficulty in accomplishing work tasks, heightened risk of infection by COVID-19, and increasingly working from home may detrimentally relate to irritation. However, personal and job resources (e.g., occupational self-efficacy, social support) may buffer. Data from 680 employees from four European countries were analyzed by means of path analyses and polynomial regression. Work intensification was significantly positively associated with cognitive and affective irritation; other job demands were not. However, working from home prior to as well as during the pandemic was related to higher cognitive irritation. None of the moderators was of meaningful significance. Reducing work intensification as well as enduring home office seems to be crucial for interventions.